The theses for PhD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
N.A. Vlasova – Features of clinical course, pathogenesis, prophylaxis and treatment of cholelithiasis on a background of hypercholesterinemia.V.Ye. Kulikov – Systemic changes of hemodynamics in patients with chronic liver diseases with portal hypertension signs.